Student Communication Pattern in Learning Process Through Social Media in Covid 19 Pandemic - Yesiana Vianingrum; Ratini Setyowati (Proceeding of International Conference on Science, Health, And Technology, 2021)
The current context under the threat of the pandemic as a result of COVID-19 is causing a series of transformations one of them is communication pattern. The government decide to close schools and campus therefore educational centers continue teaching activities from homes and use information and communication technologies. There is no direct interaction among students and students, students and teachers and other parts. The purpose of the study is to understand Student Communication Pattern in Learning Process through Social Media in Covid 19 Pandemic. This study is descriptive qualitative research, the method of the study is library research. The analyses and depictions in this study will be taken from books, journals, magazines, social media and articles that are related to the topic. The result of the study understands the student Communication Pattern in Learning Process Through Social Media in Covid 19 Pandemic.